2019
DOI: 10.1016/j.ijid.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological burden of meningococcal disease in Brazil: A systematic literature review and database analysis

Abstract: The aim of this study was to evaluate the epidemiological profile of invasive meningococcal disease (IMD) in Brazil, the first Latin American country to introduce the group C meningococcal conjugate vaccine (included in the vaccination schedule in 2010). Methods: A systematic review was conducted, covering the years 2005-2017, to identify epidemiological information on IMD and Neisseria meningitidis carriers in Brazil. Documents from the Brazilian Ministry of Health and two public databases were analyzed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 28 publications
0
21
0
3
Order By: Relevance
“…Brazil was the first country in Latin America to report an increase in the percentage of cases associated with MenW, which was evident in RS [11]. Since 2004 there has been an increase in the number of IMD cases associated with MenW in RS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brazil was the first country in Latin America to report an increase in the percentage of cases associated with MenW, which was evident in RS [11]. Since 2004 there has been an increase in the number of IMD cases associated with MenW in RS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, between 1987 and 2003, the majority of cases (73.5 %) were due to serogroup B, 25.8 % due to serogroup C and 0.7 % due to other serogroups in SC [17]. Recently, another study conducted in Brazil reported an incidence rate of 0.57 cases per 100 000 inhabitants in PR, 0.41 cases per 100 000 in SC and 0.94 cases per 100 000 in RS [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cases reported are sporadic, with seasonal variations and periodic outbreaks occurring in several cities. 6 During the last 50 years, several meningococcal vaccination programmes were implemented in Brazil, providing important lessons. In the early 1970s, an epidemic of serogroup A disease, with incidence rates as high as 179 cases/100,000 population in determined regions provided the first major experience in the world with a large-scale vaccination of a polysaccharide A and C vaccine, resulting in the successful control of the epidemic one year after its implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve serogroups of Neisseria meningitidis have been characterized based on their capsular polysaccharides, although serogroups A, B, C, W, Y and X are the most clinically significant [ 2, 3 ]. Most cases of IMD occur sporadically and vary according to the age, socioeconomic conditions, geographic regions and serogroups involved; outbreaks and epidemics may occur at irregular intervals [ 4–6 ]. Since 1975, IMD is a notifiable disease in Brazil and the National Surveillance System (SNV) monitors the epidemiological characteristics of the disease.…”
Section: Introductionmentioning
confidence: 99%